1994
DOI: 10.1073/pnas.91.12.5461
|View full text |Cite
|
Sign up to set email alerts
|

A net +1 frameshift permits synthesis of thymidine kinase from a drug-resistant herpes simplex virus mutant.

Abstract: Clinical resistance to antiviral drugs requies that a virus evade drug therapy yet retain pathogenicity. Thymidine kinase (TK)-negative mutants ofherpes simplex virus are resistant to the drug, acyclovir, but are attenuated for pathogenicity in animal models. However, numerous cases of clinical resistance to acyclovir have been associated with viruses that were reported to express no TK activity. We studied an acyclovir-resistant clinical mutant that contains a single-base insertion in its tk gene, predicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 45 publications
2
90
0
Order By: Relevance
“…Instead, it is driven by specific mRNA structure features such as rare codons [44][45][46][47][48] or mononucleotide repeat of 6 to 9 guanine nucleotides (termed G-string). 31,42,[49][50][51][52] The efficiency of incidental frameshift is usually low (i.e., <5%) although the efficiency of frame shifts at hungry codons can reach as high as 50%. 48 One of the most important examples of incidental frameshift is the frameshift on G-strings of 6 to 9 guanine nucleotides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it is driven by specific mRNA structure features such as rare codons [44][45][46][47][48] or mononucleotide repeat of 6 to 9 guanine nucleotides (termed G-string). 31,42,[49][50][51][52] The efficiency of incidental frameshift is usually low (i.e., <5%) although the efficiency of frame shifts at hungry codons can reach as high as 50%. 48 One of the most important examples of incidental frameshift is the frameshift on G-strings of 6 to 9 guanine nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…48 One of the most important examples of incidental frameshift is the frameshift on G-strings of 6 to 9 guanine nucleotides. 31,42,[49][50][51][52] Frameshifts on G-strings have been extensively studied owing to their importance in the drug resistance mechanism of ACV. 31,49-52 As mentioned earlier, HSV mutants evade the anti-viral activity of ACV primarily by inserting a G in the G7 string in their TK gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the bacteriophage examples studied, frameshifting is involved in the production of virion structural components. In certain yeast retrotransposons (see Pande et al, 1995 and references therein) and in a recently identified acyclovir-resistant isolate of herpes simplex virus type 1 (Hwang et al, 1994), + 1 ribosomal frameshifts have been documented. The available evidence suggests that + 1 frameshift sites differ both structurally and mechanistically from -1 frameshift sites and will not be discussed further in this review.…”
Section: Occurrence and Nature Of -1 Ribosomal Frameshift Signalsmentioning
confidence: 99%
“…Both viral frameshifted proteins are detectable when heterologously expressed, and LANA1 ARF is present in naturally KSHV-infected PEL cell lines. The only previous examples of frameshift products reported in DNA viruses have resulted from DNA mutations in some herpesvirus simplex type 2 and EBV strain isolates in the thymidine kinase (TK) (29) and LF3 early genes (30), respectively.…”
Section: Lana1 Generates −2 Alternative Reading Frame (Lana1 Arf ) Prmentioning
confidence: 99%